2022
DOI: 10.2215/cjn.11730921
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cells in Nephrectomy Tissue from Patients without and with a History of Urinary Stone Disease

Abstract: Background and objectives: Urinary stone disease has been associated with inflammation, but the specific cell interactions that mediate events remain poorly defined. This study compared calcification and inflammatory cell patterns in kidney tissue from radical nephrectomy specimens of patients without and with a history of urinary stone disease. Design, setting, participants, and measurements: Non-tumor parenchyma of biobanked radical nephrectomy specimens from age- and sex-matched stone formers (n=44) and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Te formation of calcium oxalate (CaOx) kidney stones is a complex biological regulatory process [1], and it includes the nucleation, growth, crystallization, and retention of crystals in the kidney [2,3]. CaOx kidney stones have two main forms: CaOx monohydrate (COM) and CaOx dihydrate (COD).…”
Section: Introductionmentioning
confidence: 99%
“…Te formation of calcium oxalate (CaOx) kidney stones is a complex biological regulatory process [1], and it includes the nucleation, growth, crystallization, and retention of crystals in the kidney [2,3]. CaOx kidney stones have two main forms: CaOx monohydrate (COM) and CaOx dihydrate (COD).…”
Section: Introductionmentioning
confidence: 99%
“…Dejban et al . [42 ▪▪ ] have taken this a step further by examining archived nephrectomy tissue samples from patients with and without a history of kidney stones. They stained the cortex and medulla to quantify areas of calcification and markers of the two main putative macrophage cell subtypes, M1 and M2: CD68 for the pro-inflammatory M1 type and CD163/206 for the anti-inflammatory M2 type.…”
Section: Introductionmentioning
confidence: 99%
“…First, Dejban et al [42 ▪▪ ] found increased calcium deposits in the kidney medulla of stone formers compared with nonstone formers (cf. Okada et al [40] cited above), although no differences in the cortex.…”
Section: Introductionmentioning
confidence: 99%
“…These studies led to the suggestion that immune mechanisms via inflammatory cells and, principally, macrophages could be involved in the calcification process in response to urinary crystals presentation to monocytes, activating macrophages and contributing to crystals phagocytosis in patients with idiopathic nephrolithiasis (6). In a well-designed study published in this issue of CJASN by Dejban et al (7), for the first time in a cross-sectional case-control study using nontumor nephrectomy tissue, samples levels of renal cortical and medullary calcium deposits were compared between various immune cell populations in both the kidney stone– and nonstone-forming populations. The results demonstrated that renal medullary calcification was higher in kidney stone formers than in nonstone formers.…”
mentioning
confidence: 99%